Vulnerability in processing definiteness: The case of heritage Turkish - Uygun, Serkan (Frontiers in Psychology, 2023)
Definiteness has been argued to be difficult for language learners to acquire because the correct usage of definiteness requires the integration of external interfaces that involve linguistic and non-linguistic information. Previous offline studies with heritage speakers have constantly reported difficulties in the use of pragmatically appropriate definite forms. The current study aims to investigate the processing of definiteness in Turkish heritage speakers via a self-paced reading experiment and to compare heritage speakers' reading times and end-of-sentence acceptance percentage to monolingually-raised Turkish speakers. The results of the experiment indicate significant differences between the heritage and monolingually-raised Turkish speakers only in the end-of-sentence acceptance percentage data but not in the reading time data. This difference between the two groups suggests that Turkish heritage speakers perform differently from the monolingually-raised Turkish speakers only in indefinite-specific sentences when they have to use their metalinguistic knowledge. These results show that heritage speakers experience vulnerability/difficulty when they have to integrate external interfaces in indefinite-specific sentences but not in definite-specific sentences.